Harmonization of the use of hunting statistics for wild boar density estimation in different study areas: Report based on comparison of case studies in different wild boar populations representative of the different management and habitat conditions across Europe. Issue 9 (23rd September 2019) - ,; Vicente, Joaquín; Palencia, Pablo; Plhal, Radim; Blanco‐Aguiar, José Antonio; Laguna, Eduardo; Soriguer, Ramón; López, Javier Fernández; Podgórski, Tomasz; Petrović, Karolina; Apollonio, Marco; Scandura, Massimo; et al.
Abstract : Hunting statistics can be suitable to determine wild boar density estimates if a calibration with an accepted rigorous method is performed. Here, densities calculated from drive counts during collective drive hunting activities are compared against density values calculated by camera trapping using the random encounter method. For this purpose, we selected 10 study sites in Spain, from North to South representing a diversity of habitats, management and hunting traditions without artificial feeding, plus one study site in Czech Republic where artificial feeding was practiced. Density values estimated from both drive counts and camera trapping were strongly positively correlated ( R 2 =0.84 and 0.87 for linear and non‐linear models, respectively) and showed a good agreement. Drive counts data might be therefore used as a density estimate to calibrate models for estimating density in large areas and potentially, to compare densities among areas. For these purposes, there is still the need to harmonise hunting data collection across Europe to make them usable at a large scale. Our results need to be confirmed across a wider number of European populations to provide valid geographical wild boar density predictions across Europe.